Lot Quality Assurance Sampling to Monitor Supplemental Immunization Activity Quality: An Essential Tool for Improving Performance in Polio Endemic Countries. (1st November 2014) - Brown, Alexandra E.; Okayasu, Hiromasa; Nzioki, Michael M.; Wadood, Mufti Z.; Chabot-Couture, Guillaume; Quddus, Arshad; Walker, George; Sutter, Roland W.
Abstract : Monitoring the quality of supplementary immunization activities (SIAs) is a key tool for polio eradication. Regular monitoring data, however, are often unreliable, showing high coverage levels in virtually all areas, including those with ongoing virus circulation. To address this challenge, lot quality assurance sampling (LQAS) was introduced in 2009 as an additional tool to monitor SIA quality. Now used in 8 countries, LQAS provides a number of programmatic benefits: identifying areas of weak coverage quality with statistical reliability, differentiating areas of varying coverage with greater precision, and allowing for trend analysis of campaign quality. LQAS also accommodates changes to survey format, interpretation thresholds, evaluations of sample size, and data collection through mobile phones to improve timeliness of reporting and allow for visualization of campaign quality. LQAS becomes increasingly important to address remaining gaps in SIA quality and help focus resources on high-risk areas to prevent the continued transmission of wild poliovirus.